Violence Elsewhere 1 : Imagining Distant Violence in Germany 1945-2001 - Bielby, Clare (2024)
Explores the significance of postwar German representations of violence in other places and times. Germany's twentieth-century history has made imagining and representing violence in German culture challenging, meaning that it can be difficult to locate and explore critically the significance of violence in and for the postwar German states. This volume approaches that challenge through critical analysis of "violence elsewhere," that is, constructions of violence in distant, imagined, or temporally distinct times and places. Such representations have offered a stage on which to imagine violence. Moreover, German representations of "violence elsewhere" are simultaneously images of Germany itself, revealing something about otherwise submerged meanings and functions of violence in German culture. The essays in this volume explore selected, emblematic works from East, West, and, later, unified Germany, which imagine violence in, for example, Latin America, Vietnam, Cambodia, the USA, and the Middle East, as well as in the respective "other" German state and in the German past. Drawing on fields including cultural, literary, film, visual, and gender studies, it introduces multidisciplinary theoretical approaches to the topic of violence elsewhere that may be transferable beyond German studies too. As such, the volume allows us to reflect more broadly on relationships between violence, culture, community, and the creation of identities, and to look beyond binary notions of "here" and "elsewhere," "self" and "other." It thus expands our understanding of what German culture is and could be. Edited by Clare Bielby and Mererid Puw Davies. Contributors: Seán Allan, Martin Brady, Evelien Geerts, Katharina Karcher, J.J. Long, Ernest Schonfield, and Katherine Stone. Chapter 8, "Problematizing Political Violence in the Federal Republic of Germany: A Hauntological Analysis of the NSU Terror and a Hyper-Exceptionalized "9/11" is available as Open Access under the Creative Commons license CC BY-NC-ND. The open access version of this publication was funded by the European Research Council. This book is available as Open Access under the Creative Commons license CC BY-NC-ND.